Predatory mites (Acari: Mesostigmata) associated with Polyphagotarsonemus latus (Prostigmata: Tarsonemidae) on solanaceous Plants - Silva, Abraao S.; Tavares, Swamy R. S. A.; Lofego, Antonio C. [UNESP]; Almeida, Emanuel H. N.; Silva, Edmilson S. (Systematic & Applied Acarology Soc London, Natural History Museum, 2016)
Vegetables of the family Solanaceae are particularly at risk from pest infestations. Among these pests, mites stand out, species Polyphagotarsonemus latus (Banks) (Prostigmata: Tarsonemidae). Attacks by this pest reduce agricultural yield and require the use of control measures. Predatory mites of the family Phytoseiidae have been identified and used in several countries as biological control agents of mites, whiteflies and thrips. The objective of the present study was to identify the occurrence of predatory mites associated with P. latus on solanaceous plants. Samples were collected from bell pepper (Capsicum annum L.), chili (C. frutescens L.) and eggplant (Solanum melongena L.). Sampling was carried out in the municipalities of Arapiraca, Feira Grande, Limoeiro de Anadia, and Sao Sebastiao, all in the state of Alagoas, northeastern Brazil. Samples were collected every two weeks, from June to September 2014. A total of 9,316 mite specimens was found, comprising 579 specimens of Mesostigmata and 8,737 phytophagous mites identified as P. latus. Among the Mesostigmata, 565 belonged to the family Phytoseiidae and ten to the family Ascidae. The phytoseiids were classified into 15 species of seven genera; 14 of the genera belonged to Amblyseiinae and only one to Phytoseiinae. The ascids were represented by two morphospecies of two genera. Fifty-two percent of the Mesostigmata were found on eggplants. Polyphagotarsonemus latus was found in large numbers on all crops.
Keywords: Phytoseiidae; Broad mite; Acari; Tarsonemidae